LDAP programming with Java - Weltman, Rob, 1953- (Addison-Wesley, 2000)
In this book, the creators of the Directory SDK for Java show how it can be used to build powerful, standards-based directory applications that leverage LDAP directory information on intranets, the Internet, even in E-commerce applications. Start by reviewing what Directories are, what directory-enabled applications can accomplish, and the key elements of the LDAP directory standard. Next, establish a directory application development environment; learn how the Directory SDK for Java can be used to build LDAP-enabled applications; and walk through retrieving, creating, maintaining, and securing directory information. Along the way, developers will learn how to build LDAP-aware applets; script LDAP with JavaScript and Java; use LDAP on a Web server; create reusable LDAP JavaBeans; optimize the performance of their LDAP-enabled applications; and much more. For all intermediate to advanced Java and network programmers, system, network, and messaging administrators.